Heavily Substituted Atropisomeric Diarylamines by Unactivated Smiles Rearrangement of N‐Aryl Anthranilamides. (6th September 2017) - Costil, Romain; Dale, Harvey J. A.; Fey, Natalie; Whitcombe, George; Matlock, Johnathan V.; Clayden, Jonathan
Abstract: Diarylamines find use as metal ligands and as structural components of drug molecules, and are commonly made by metal‐catalyzed C−N coupling. However, the limited tolerance to steric hindrance of these couplings restricts the synthetic availability of more substituted diarylamines. Here we report a remarkable variant of the Smiles rearrangement that employs readily accessible N‐aryl anthranilamides as precursors to diarylamines. Conformational predisposition of the anthranilamide starting material brings the aryl rings into proximity and allows the rearrangement to take place despite the absence of electron‐withdrawing substituents, and even with sterically encumbered doubly ortho‐substituted substrates. Some of the diarylamine products are resolvable into atropisomeric enantiomers, and are the first simple diarylamines to display atropisomerism. Abstract : Tolerant und kompatibel : Die Smiles‐Umlagerung von konformativ prädisponierten Anthranilamiden ist eine wertvolle Methode für die Synthese von Diarylaminen, sogar solchen mit unaktivierten oder stark substituierten migrierenden Ringen.